Terapi Isometric Handgrip Exercise untuk Nyeri Akut pada Hipertensi di Roujin Home X - Faizal Dwi Cahyo; Ita Apriliyani; Arni Nur Rahmawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Introduction: The increase in life expectancy among the elderly has directly contributed to the rise in the global elderly population. According to global data, the number of elderly individuals is projected to reach 1.4 billion by 2030. This demographic growth is often accompanied by various health problems associated with aging, such as the decline in vital organ function and the emergence of degenerative diseases. One of the most common degenerative diseases among the elderly is hypertension. Hypertension is widely known as a “silent killer” because it can lead to serious complications, including stroke and heart disease, if not managed properly. A common complaint experienced by individuals with hypertension is headache, particularly in the posterior region, which significantly affects the patient’s quality of life. Management of hypertension can be carried out through pharmacological therapy with antihypertensive drugs as well as non-pharmacological interventions. One of the non-pharmacological approaches increasingly being applied is isometric handgrip exercise, which involves static muscle contractions performed at light to moderate intensity. Method:This study aimed to evaluate the effect of isometric handgrip exercise on pain reduction in patients with hypertension. The research design employed a descriptive case study involving one individual with hypertension who experienced pain complaints. The study was conducted on September 16–18, 2024, at Roujin Home X. The instruments used included observation, interview, and the provision of isometric handgrip exercise therapy. Pain measurement was carried out using a numerical rating scale before and after the intervention. Results:The three-day intervention demonstrated a significant reduction in pain levels. On the first day, the patient reported a pain score of 6, which decreased to 4 on the second day, and further declined to 2 on the third day after the intervention. Conclusion:The findings of this study indicate that isometric handgrip exercise is an effective non-pharmacological method for alleviating acute pain in patients with hypertension. This simple intervention has the potential to be applied as a complementary therapy in elderly care facilities to improve the quality of life of individuals living with hypertension.